2005
DOI: 10.1251/bpo104
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of integrin-linked kinase in capillary/tube-like network formation of human vascular endothelial cells

Abstract: Angiogenesis is a complex process involving an ECM and vascular endothelial cells (EC), and is regulated by various angiogenic factors including VEGF. The ability to form a capillary/tube-like network is a specialized function of EC. Therefore, in vitro angiogenesis was assessed by a capillary/tube-like network formation assay. There are three angiogenic parameters: capillary length, number of capillaries, and relative capillary area per field. We evaluated capillary length per field in the assay. VEGF promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 20 publications
0
8
0
2
Order By: Relevance
“…An in vitro study using bovine aortic EC showed that siRNA-mediated silencing of ILK increased cell adhesivity to a variety of specific matrix substratum components (collagen I, vitronectin, fibronectin, and fibrinogen) but impaired cell spreading, migration, and capillary morphogenesis; these effects were attributed to destabilization of cell matrix through alterations in surface distribution of ␣v␤3 and ␣5␤1 integrins and were not accompanied by changes in Akt or Ser-9 GSK3␤ phosphorylation (27). In HUVEC, ILK was shown to associate with VEGF receptor (57), whereas transduction with dominant negative, kinase deficient ILK, or pharmacological inhibition of ILK resulted in inhibition of a number of VEGFinduced responses, including adherence to collagen 1, phosphorylation of Ser-473 Akt, migration, survival, proliferation, and capillary morphogenesis (35,57,60). In both HUVEC and endothelial progenitor cells, ILK plays a key role in cell survival signaling responses ( Ser-473 Akt or Ser-9 GSK3␤ phosphorylation) to anchorage deprivation, nutrient deprivation or hypoxia; furthermore, with the use of a model of mouse hind limb ischemia, ILK was demonstrated to promote endothelial progenitor cell recruitment and neovascularization of ischemic tissue (61,62).…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro study using bovine aortic EC showed that siRNA-mediated silencing of ILK increased cell adhesivity to a variety of specific matrix substratum components (collagen I, vitronectin, fibronectin, and fibrinogen) but impaired cell spreading, migration, and capillary morphogenesis; these effects were attributed to destabilization of cell matrix through alterations in surface distribution of ␣v␤3 and ␣5␤1 integrins and were not accompanied by changes in Akt or Ser-9 GSK3␤ phosphorylation (27). In HUVEC, ILK was shown to associate with VEGF receptor (57), whereas transduction with dominant negative, kinase deficient ILK, or pharmacological inhibition of ILK resulted in inhibition of a number of VEGFinduced responses, including adherence to collagen 1, phosphorylation of Ser-473 Akt, migration, survival, proliferation, and capillary morphogenesis (35,57,60). In both HUVEC and endothelial progenitor cells, ILK plays a key role in cell survival signaling responses ( Ser-473 Akt or Ser-9 GSK3␤ phosphorylation) to anchorage deprivation, nutrient deprivation or hypoxia; furthermore, with the use of a model of mouse hind limb ischemia, ILK was demonstrated to promote endothelial progenitor cell recruitment and neovascularization of ischemic tissue (61,62).…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenesis is driven by the tumor's release of vascular endothelial growth factor (VEGF), which binds to the receptors on endothelial cells of nearby blood vessels causing the endothelial cells to proliferate and bud from the existing blood vessel, and migrate toward the source of proangiogenic signal. ILK regulates hypoxia-inducible factor 1 alpha subunit (HIF-1a)-mediated VEGF expression in glioblastoma and prostate cancer cells, and is essential for VEGFstimulated endothelial cell migration, tube formation and tumor angiogenesis (Tan et al, 2004;Koul et al, 2005;Watanabe et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Results of VEGF treatment showed that RCE cells formed a capillary-like network after continual stimulation by 10 ng/mL of VEGF 165 for 2 passages. Because the formation of a capillary-like network is the specialized function of endothelial cells [27,30,31] , the RCE cell line established here is indeed an endothelial cell line. This conclusion is coincident with that of human vascular endothelial cells differentiated from human adipose tissue derived mesenchymal stem cells reported by Guan et al [43] .…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al (2002) [30] found that human umbilical vein endothelial cells being cultured on matrigel formed an elaborate capillary-like network at the light microscopic level after treatment with VEGF 165 . In 2005, Watanabe et al [31] postulated that formation of a capillary-like network was a specialized function of endothelial cells, and VEGF promoted the network formation of endothelial cells cultured in different types of gel matrix. Therefore, in vitro formation of a capillary-like network has become a morphological marker for endothelial cell identification.…”
mentioning
confidence: 99%